Elemental Sulfur Recommendations for Sugarcane on Florida Organic Soils - James Mabry McCray (EDIS, 2019)
Micronutrient deficiencies can be important limiting factors in alkaline soils, with most micronutrients becoming less available for plant uptake as soil pH increases. This 6-page document is intended primarily for Florida sugarcane growers but may also be useful to researchers and others interested in sugarcane nutrition. It presents revised elemental sulfur recommendations for sugarcane grown on Florida organic soils along with supporting information. Written by J. Mabry McCray, and published by the UF/IFAS Agronomy Department, February 2019. http://edis.ifas.ufl.edu/ag429